KOLEKSI BAHAN PUSTAKA DALAM MENUMBUHKAN MINAT BACA SISWA DI UPT SMP NEGERI 38 MEDAN - Muhammad Hafizh Amrul (Universitas Islam Negeri Sumatera Utara Medan, 2022)
AbstractThe collection of school library materials is a place for providing information that plays a very important role in fostering student interest in reading. However, the problems that occur are still the weakness of human resources and the lack of collection of library materials so that it can result in a lack of student interest in the library, therefore good library management and the completeness of library materials will lead to student interest in reading. The purpose of this study was to determine the collection of library materials and the strategy of the head of the library in fostering student interest in reading at UPT SMP Negeri 38 Medan. This type of research is qualitative with a descriptive approach. Data collection techniques in this study were observation, interviews and documentation. The results showed that the strategy used by the head of the library was to determine the library work program, provide training, accept street vendors from library science, cooperate with the provincial library, cooperate with teachers and give rewards to students who frequently visited the library. Constraints faced in the library management process in increasing student interest in reading at UPT SMP Negeri 38 Medan are the lack of permanent staff in the library, incomplete library facilities, inadequate facilities and infrastructure, limited library space. It is hoped that this research can be continued by the parties concernedKeywords: Book Collection, Library Materials, Student Reading Interest